(untitled) (Biological Sciences - PJSIR, 2002)
Palm tree is a "Wonder" tree that is very useful to man. The fruit of this tree is edible and leaves are used for making roofs, mats, baskets, walls etc. The wood can be used to make fence, furniture, bridge etc. The sap makes a pleasant drink, and palm wine can be made from it. Palm sugar is obtained from the sap of several species of palm in tropical regions of the world (African Encyclopedia 1974). The chief sugar found in the sap is sucrose, present between 10-16% (Stewat 1987). The wine from Felled palm tree is obtained by tapping the base of the inflorescence of the stemjust below the terminal leaves. Before the tapping, there are preliminary processes, which must be carried out. For example the Felled palm tree is left to age for about five days after a hole is made at the point of tapping thereby at the end of about 24 hours and the juice starts coming out, which is collected in a suitable container (Oshodi 1986).